2016
DOI: 10.1159/000445752
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial to Mesenchymal Transition in Clear Cell Renal Cell Carcinoma with Rhabdoid Features

Abstract: Aims: The aims of this study were to investigate the association of renal cell carcinoma (RCC) displaying rhabdoid features and morphologically mesenchymal characteristics with epithelial to mesenchymal transition (EMT), and to clarify the expression of EMT markers. Methods: We investigated the expression of EMT markers (E-cadherin, vimentin, Snail, Slug, ZEB1, ZEB2 and Twist1) using immunohistochemistry, Western blotting and real-time polymerase chain reaction in 18 cases of clear cell RCC (ccRCC) with rhabdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Loss of epithelial cell characteristics makes it difficult for cells to adhere, and the acquisition of interstitial cell characteristics makes it easier for cells to metastasize. 18 Numerous molecular alternations occur in the process of EMT, such as the loss or low E-cadherin Figure 3 CSE can activate the ERK5/AP-1 signaling pathway. (A) t-ERK5, -fos and -jun levels were notably decreased depending on the CSE dose.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Loss of epithelial cell characteristics makes it difficult for cells to adhere, and the acquisition of interstitial cell characteristics makes it easier for cells to metastasize. 18 Numerous molecular alternations occur in the process of EMT, such as the loss or low E-cadherin Figure 3 CSE can activate the ERK5/AP-1 signaling pathway. (A) t-ERK5, -fos and -jun levels were notably decreased depending on the CSE dose.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of epithelial cell characteristics makes it difficult for cells to adhere, and the acquisition of interstitial cell characteristics makes it easier for cells to metastasize. 18 Numerous molecular alternations occur in the process of EMT, such as the loss or low E-cadherin expression as well as the up-regulated N-cadherin expression, referred to as “cadherin switch”, which is typically observed during EMT via the interruption of tight junctions and the concomitant gain of cell motility. In vitro IHC had been carried out to evaluate levels of N-cadherin, E-cadherin, Vimentin, as well as ZO-1 EMT markers in RCC specimens, proving that they correlated with the prognosis of patients with RCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mounting evidence has indicated that ZEB2 is involved in the initiation and development of malignancies (8). Furthermore, it has been reported that ZEB2 promotes the epithelial-mesenchymal transition (EMT), a pathological process leading to specific morphological and phenotypic alterations during cancer metastasis in tumor cells (9,10). According to previous studies, ZEB2 was significantly upregulated in LSCC (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…The membranes were then incubated overnight at 4°C with secondary antibodies. The bound antibody was visualized using an ECL kit (GE Healthcare Bio-Sciences) and the membranes were exposed to X-ray film (GE Healthcare Bio-Sciences) 18 - 20 . The protein levels were standardized by actin using an image analyzer (Ez-Capture MG; ATTO, Tokyo), and the expression signal relative to the standardized signal was regarded as the level of expression for each sample.…”
Section: Methodsmentioning
confidence: 99%